Pengaruh Debt Financing, Equity Financing Non Performing Financing Terhadap Profit Expense Ratio Pada Bank - Situmorang, Nurul Utami; Atika, Atika; Yanti, Nur Santri (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2024)
The aim of this research is to determine the influence of the level of Debt Financing (DF), Equity Financing (EF), and Non-Performing Financing (NPF) on the Profit Expense Ratio (PER) at Bank Muamalat in Indonesia. This type of research is quantitative research. A quantitative approach is an approach that emphasizes testing theories or hypotheses through measuring research variables in numbers and analyzing data using static procedures and systematic modeling. The results of this research indicate that partially the Debt Financing variable does not have a significant effect on the Profit Expence Ratio at PT. Bank Muamalat in 2018-2022. The results of this research indicate that partially the Equity Financing variable does not have a significant effect on the Profit Expence Ratio at PT. Bank Muamalat in 2018-2022. The results of this research show that partially the Non Performing Financing variable has a significant effect on the Profit Expence Ratio at PT. Bank Muamalat in 2018-2022. The results of this research show that simultaneously the variables Debt Financing, Equity Financing, and NPF have a significant effect on the profit expense ratio at PT. Bank Muamalat in 2018-2022.